EVALUASI KEBIJAKAN DANA BANTUAN OPERASIONAL SEKOLAH (BOS) PADA SEKOLAH NEGERI DI KECAMATAN PALU TIMUR - Soulisa, Nurmala Sari (Katalogis, 2017)
The objective of the research is to analyze the policy evaluation of school operational assistance to elementary schools at District of Palu Timur. The method of the research is qualitative method. The informants of the research are Sector Chiefs of Elementary Education, Head of Sub- Administarative Program and planning, principal at SDN 24 Palu, Principal at SDN 15 Palu, School Comittee,and parents. The data of the research are primary data and secondary data. The techniques of data collection are observation, interview, and documentation. This research describes BOS fund at the schools assest using policy evaluation, namely effectiveness, efficiency, adequacy, flattening, responsivity, and accuracy. Based on six criterias above can be known that from the objective of BOS fund policy is running well. But, it is not optimal yet in the implementation, it can not show an increasing to good and excellent education services.